1996
DOI: 10.3109/08958379608995209
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods of Determining and Predicting the Pathogenicity of Mineral Fibers

Abstract: Most authors consider that long-term inhalation studies represent the most reliable method of obtaining data on the pathogenicity of mineral fibers. However, because of the length of time required and the great cost of inhalation work, other methods of examining the biological effects of mineral fibers have been used. The program of work described here was designed to compare a wide range of techniques, including inhalation, for determining the biological effects of a selection of man-made mineral fibers. Sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 15 publications
4
31
0
1
Order By: Relevance
“…In our study the proliferative response to code 100/475 was no greater than that in unexposed control animals, whereas amosite and SiC both produced significant increases in proliferation. In a concurrent study (14), we showed that deposition, in terms of the numbers of fibers greater than 10 pm recovered from lungs at the end of a 12-month inhalation at 1000 fibers/ml, was roughly equivalent for the three fiber types. However, the code 100/475 microfiber differed from long amosite and SiC in the very high numbers of fibers that were less than 5 pm in length.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our study the proliferative response to code 100/475 was no greater than that in unexposed control animals, whereas amosite and SiC both produced significant increases in proliferation. In a concurrent study (14), we showed that deposition, in terms of the numbers of fibers greater than 10 pm recovered from lungs at the end of a 12-month inhalation at 1000 fibers/ml, was roughly equivalent for the three fiber types. However, the code 100/475 microfiber differed from long amosite and SiC in the very high numbers of fibers that were less than 5 pm in length.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence is emerging from both in vitro (21,22) and in vivo (14,23) studies that SiC whiskers can be as toxic as asbestos fibers. In this study we examined a number (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in LDH in the supernatants of RAW 264.7 cells exposed to high concentrations of PT or SiC were confirmed in this study at relatively lower levels. In inhalation studies of PT and SiC in rats, pulmonary fibrosis 26) , and mesotheliomas and pulmonary fibrosis 27) were observed, respectively. This suggested the possible injurious nature of PT and SiC to the lungs.…”
Section: Discussionmentioning
confidence: 99%